1997
DOI: 10.1046/j.1365-2427.1997.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Grazer control and nutrient limitation of phytoplankton biomass in two Australian reservoirs

Abstract: 1. Grazer and nutrient controls of phytoplankton biomass were tested on two reservoirs of different productivity to assess the potential for zooplankton grazing to affect chlorophyll/phosphorus regression models under Australian conditions. Experiments with zooplankton and nutrients manipulated in enclosures, laboratory feeding trials, and the analysis of in‐lake plankton time series were performed. 2. Enclosures with water from the more productive Lake Hume (chlorophyll a = 3–17.5 μg l–1), revealed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 3 publications
4
41
0
Order By: Relevance
“…Limitation was related to the time of year with nutrients controlling primary production during late spring and early summer. Both nitrogen and phosphorus can limit phytoplankton growth in deep storages such as Lakes Dartmouth and Hume (Matveev & Matveeva, 1997) and Chaffey Dam (Sherman et al, 2001).…”
Section: Nutrient Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitation was related to the time of year with nutrients controlling primary production during late spring and early summer. Both nitrogen and phosphorus can limit phytoplankton growth in deep storages such as Lakes Dartmouth and Hume (Matveev & Matveeva, 1997) and Chaffey Dam (Sherman et al, 2001).…”
Section: Nutrient Limitationmentioning
confidence: 99%
“…There are now a number of studies from Australia that show the potential for zooplankton grazers to control phytoplankton. In particular, it has been shown that Daphnia carinata, a large cladoceran, can be present in high densities in Australian systems (Mitchell & Williams, 1982) and that it effectively grazes phytoplankton (e.g., Ganf & Shiel, 1985;Merrick & Ganf, 1988;King & Shiel, 1993;Kobayashi, 1993;Kobayashi et al, 1996Kobayashi et al, , 1998Matveev & Matveeva, 1997). In addition, D. carinata is able to feed on cyanobacteria (Kobayashi, 1993) while being resistant to certain cyanobacterial toxins (Matveev et al, 1994b).…”
Section: Food Chain Interactions -Biomanipulationmentioning
confidence: 99%
“…a concentration from a shallow lagoon located near Lake Waihola. In two Australian reservoirs the biomass of D. carinata explained >50% of the variance in phytoplankton biomass (Matveev & Matveeva 1997). Inverse relationships between concentrations of Daphnia and Chl.…”
Section: Discussionmentioning
confidence: 96%
“…Inverse relationships between concentrations of Daphnia and Chl. a indicate that the grazing activities of Daphnia may significantly reduce the biomass of phytoplankton (Tessier 1983;Folt et al 1993;Matveev & Matveeva 1997).…”
Section: Discussionmentioning
confidence: 99%
“…According to Matveev (2003), the lakes of the Southern Hemisphere have been investigated less intensively, but provide results which either support (Hansson 1992;Jeppesen et al 2000;Matveev 1998;Matveev and Matveeva 1997;Quiros 1990;Rowe and Champion 1993) or do not support (Burns 1998;Matveev 1995Matveev , 2003Matveev et al 1994b) existing models. Matveev (2003) suggested any unsupportive results might have been due to the differences in fish and zooplankton fauna of the Southern Hemisphere and the limnology of some lakes.…”
Section: Food Web Theory Concerning Biomanipulationmentioning
confidence: 99%